Vasodilatation induced by croton schiedeanus schlecht associated with metabolic way of guanylate cyclase (2012)
The EtOH extract of Croton shiedeanus Schlecht, medicinal species used by the popular tradition in Colombia for hypertension, relaxes vascular rings of Wistar rat aorta stimulated with phenylephrine (10-6 M, alpha adrenergic receptor agonist), in a dose-depending manner, with an EC50 of 1.3 × 10-5 g/mL. This effect is superior to that exercised over rings stimulated with KCl (6,0 × 10-2 M, voltage-dependent calcium channel activator) and is reduced in vascular rings without endothelium. The vascular relaxation is reversed in the presence of methylene blue (1.0 × 10-4 M, guanylate cyclase inhibitor) and L-NAME (10-4 M, nitric oxide synthase inhibitor), and is not affected in presence of propranolol (10-6 M, beta receptor antagonist), atropine (30 × 10-5 M, muscarinic antagonist) and indomethacin (10-6 M, cyclooxygenase inhibitor). Additionally, the contractions induced by CaCl2 (10-5 – 10-2 M, calcium currents activator) are not affected in the presence of EtOH C. schiedeanus extract (5.0 × 10-5 g/mL). Serial dilutions of L-NAME and methylene blue (until 10-14 M) show that C. schiedeanus recovers almost entirely the vasodilator effect in presence of L-NAME but not in presence of methylene blue (91 versus 68% of Emax, respectively). In addition, the relaxant potency and efficacy of C. schiedeanus is greater than its predominant active metabolite, ayanin (IC50: 1,3 vs. 4,9 × 10-5 g/mL, Emax: 100 vs. 67%). These findings suggest that C. schiedeanus exerts vasodilating effects, particularly related to the metabolic pathway of guanylate cyclase and gives support the traditional use of this species.